Supported and Free-Standing Non-Noble Metal Nanoparticles and Their Catalytic Activity in Hydroconversion of Asphaltenes into Light Hydrocarbons - Leonid Kustov; Andrei Tarasov; Kristina Kartavova; Valery Khabashesku; Olga Kirichenko; Gennady Kapustin; Alexander Kustov; Evgeny Abkhalimov; Boris Ershov (Crystals)
The hydroconversion of asphaltenes into light hydrocarbons catalyzed by supported and free-standing non-noble metal nanoparticles was studied. The activity of Ni or Co immobilized on microspherical oxide carriers and Co nanoparticles dispersed in a hydrocarbon solution of asphaltene was found to be higher than that of a comparative Pt-Pd/Al2O3 catalyst. The yield of light products (C5+) reached up to 91% on cobalt nanoparticles supported onto alumina microspheres.